Comparison between reliability index and load rating for evaluation of structural security of bridges using diagnostic load tests: Case of study in Costa Rica - Bolaños-Ávila, Darnel G. (2019)
In the present work two methods for structural safety evaluation are applied (load rating and reliability index) on the same bridge which was applied a diagnostic load test with two different configurations of truck’s position. The aim is to compare the results and discuss about the limitations of each one and finally recommend cases where each method is more useful. Likewise accentuate the benefits of using load test for bridge condition evaluation with respect to the methodology that is in use in Costa Rica. The methods were evaluated for failure of flexure on the prestressed concrete beams. Besides it was developed a bridge model in the software CSi Bridge 2017® to compare the expected results with the obtained in the load test. The results show that the bridge has differences between the theoretical and real deformations, due to the stiffness of non-structural elements. The bridge has an excellent condition according to both methods. It concludes that the reliability index is better for structural safety evaluation, for its correlations for each bridge.